Transformasi Manajemen Pendidikan Berbasis Kecerdasan Buatan (Artificial Intelligence) - Dedy Yusuf Aditya; Muhammad Tri Habibie (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The development of Artificial Intelligence (AI) has driven significant transformation in various aspects of educational management, including educational human resource management. This study aims to analyze the trends, implementation forms, benefits, challenges, and opportunities of AI utilization in educational human resource management through a Systematic Literature Review (SLR) approach. The study adopted the PRISMA 2020 guidelines through identification, screening, eligibility assessment, and article inclusion stages. Data were collected from Google Scholar, Scopus, and ScienceDirect databases covering publications from 2020 to 2026. Based on the selection process, 20 articles met the inclusion criteria and were analyzed using content analysis and thematic synthesis. The findings indicate that AI applications in educational human resource management include teacher recruitment and selection, performance evaluation, professional development, talent management, and data-driven decision support systems. In addition to improving efficiency, objectivity, and decision-making quality, AI implementation also faces several challenges, including data privacy and security, algorithmic bias, human resource readiness, and technological infrastructure limitations. This study concludes that AI has substantial potential to enhance the effectiveness of educational human resource management; however, its successful implementation requires digital leadership, competent human resources, effective data governance, and supportive policies. The findings are expected to provide valuable insights for educational institutions in developing adaptive human resource management systems in the digital era.